2018
DOI: 10.1177/1045389x18812704
|View full text |Cite
|
Sign up to set email alerts
|

Interphase influences on the mechanical behavior of carbon nanotube–shape memory polymer nanocomposites: A micromechanical approach

Abstract: The effects of interphase characteristics on the elastic behavior of randomly dispersed carbon nanotube–reinforced shape memory polymer nanocomposites are investigated using a three-dimensional unit cell–based micromechanical method. The interphase region is formed due to non-bonded van der Waals interaction between a carbon nanotube and a shape memory polymer. The influences of temperature, diameter, volume fraction, and arrangement type of carbon nanotubes within the matrix as well as two interphase factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 64 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…Several studies have found that this low transition is attributed to the strong interfacial interactions between polymer chains and nanoparticles producing an immobilized layer adsorbed on the surface of nanoparticles. The formation of interphase and its efficiency on the mechanical and electrical properties of polymer nanocomposites have been reported in the previous articles . The interphase regions accelerate the percolation threshold and expand the networks .…”
Section: Introductionmentioning
confidence: 60%
“…Several studies have found that this low transition is attributed to the strong interfacial interactions between polymer chains and nanoparticles producing an immobilized layer adsorbed on the surface of nanoparticles. The formation of interphase and its efficiency on the mechanical and electrical properties of polymer nanocomposites have been reported in the previous articles . The interphase regions accelerate the percolation threshold and expand the networks .…”
Section: Introductionmentioning
confidence: 60%
“…By substituting equation ( 29) into (20), the total number of entanglements (N) as functions of temperature (T) and stretch ratio (  ) can be obtained as,…”
Section: Above the Tgmentioning
confidence: 99%
“…However, the interfacial reactions, coupled confinements and coordinative motions of nanoparticles within the polymer matrix have not been fully understood [17,18]. A micromechanical model was previously utilized to study the interphase influences on the mechanical behavior of SMP nanocomposite, and the environmental conditions were considered in the modelling process [19,20]. Monte Carlo simulation was also used to study the percolation behavior of SMP nanocomposite reinforced by carbon black [21].…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, only non-bonded electrostatic and van der Waals (vdW) interactions are reflected between the CNT and polymer matrix [33,34]. Because of the fact that vdW interactions contribute more extremely in three higher orders of magnitude than electrostatic energy, the electrostatic interactions are ignored in comparison with vdW interactions [35][36][37]. In the micromechanics approaches, an equivalent solid continuum interphase is usually taken into account between the CNT and the polymer matrix characterizing the vdW interactions [34,36,38,39].…”
Section: Introductionmentioning
confidence: 99%